PEMBELAJARAN INOVATIF PADA KURIKULUM MERDEKA DI SEKOLAH DASAR NEGERI CIBUBUR 11 PAGI - Salamah, Alya; Aulia Sakinah, Jihan; Lillian Harvani Santoso, Talitha; Nur Alifa, Fathiya; Puput Anggraini, Dwi; Dwiprabowo, Risky (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the implementation of the Merdeka Curriculum at SDNCibubur 11 Pagi, East Jakarta, and the school's strategies in facing 21st-centuryeducational challenges. The main focus of this study includes learningtransformation through the concept of deep learning, integration of digitaltechnology, and strengthening school culture through the Pancasila StudentProfile. The method used is descriptive qualitative through observation of schoolactivities and internal policy analysis. Results indicate that SDN Cibubur 11 Pagihas successfully adopted curriculum flexibility through the preparation of one-pageDeep Learning Plans (RPM) and the utilization of interactive devices such asInteractive Flat Panels (IFP). Efforts to improve teacher competence are carriedout collectively through the "Jumat Belajar" (Jumber) program. Despite constraintsin limited technological facilities and the adaptation of senior teachers, the schooltakes anticipatory steps through systematic budget management and teachercollaboration. A structured school culture through daily activities and the 5Scharacter strengthening serves as an essential foundation in achieving theschool's vision of being intelligent, characterized, and innovative.